Student Motivation In Using The "Line People Nearby" Dating Application As An Effort To Build New Relationships - Kurniasari, Febriayu Vina; Aesthetika, Nur Maghfirah (Procedia of Social Sciences and Humanities, 2024)
Dating apps have significantly changed the dynamics of interpersonal interactions, and the reasons why people use these programs vary, including the desire to find a mate, expand their social circle, or simply satisfy their curiosity. The People Nearby feature in the Line app is specifically aimed at fostering deeper relationships and increasing social interaction. Motivational needs consist of five levels, namely basic needs, security needs, social needs, needs to be rewarded and finally the need to self-actualize. In this research, researchers used Abraham Maslow's theory of motivation to determine the motivation of Communication Science students at Muhammadiyah University of Sidoarjo to use the Line People Nearby dating application. The purpose of the research entitled student motivation in using the dating application “Line People Nearby” as an effort to build new relationships, namely researchers want to analyze the motivation of Communication Science students at Muhammadiyah Sidoarjo University in using the Line People Nearby dating application. The type of method used by researchers uses qualitative research methods. The researcher concluded that all informants had embraced Maslow's theory of needs, starting from basic needs, the need for security, social needs, taste needs, wanting to get a sense of reward. However, some informants fall into the category of social needs (a sense of love, affection, and ownership rights)